A Review on Impurity Profiling In Pharmaceutical Substances - Shounak R. Mande; Shankar S. Yelmame; Laxmikant B. Borse, Laxmikant B. Borse (Asian Journal of Pharmaceutical Research and Development, 2024)
The term "impurity profiling" describes a group of analytical techniques aimed at detecting, identifying, and quantifying residual solvents and organic and inorganic impurities in bulk medications and pharmaceutical formulations. This is the main objective of contemporary drug analysis since it is the most effective method of characterizing the stability and quality of pharmaceutical formulations and bulk drugs. To monitor them, certain analytical methods have to be developed. Even in cases where synthesis, formulation, or production procedures are improved, new purities may emerge from changes made to them. The International Conference on Harmonization (ICH), the US Food and Drug Administration (FDA), and other regulatory organizations are closely monitoring the identification of contaminants in Active Pharmaceutical Ingredients (APIs) and the requirements for their purity. In addition to degraded end products obtained during manufacture, pharmaceutical goods may contain impurities from a range of sources, such as ligands, heavy metals (HMs), catalysts, reagents, and other components like filter aids and similar compounds. The permissible quantities of pollutants found in APIs or formulations are progressively being limited by a number of pharmacopoeias, including the American, British, and Indian pharmacopoeias. Pharmaceutical contaminants are separated and analyzedby employingvarious techniques, that includes infrared spectroscopy, nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry, ultracold extraction column chromatography, and ultraviolet spectrometry. For impurity profiling, this is the hyphenated method that is most frequently employed.